2018
DOI: 10.3389/fimmu.2018.00653
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Protein Containing B-Cell Epitopes of Different Loxosceles Spider Toxins Generates Neutralizing Antibodies in Immunized Rabbits

Abstract: Loxoscelism is the most important form of araneism in South America. The treatment of these accidents uses heterologous antivenoms obtained from immunization of production animals with crude loxoscelic venom. Due to the scarcity of this immunogen, new alternatives for its substitution in antivenom production are of medical interest. In the present work, three linear epitopes for Loxosceles astacin-like protease 1 (LALP-1) (SLGRGCTDFGTILHE, ENNTRTIGPFDYDSIMLYGAY, and KLYKCPPVNPYPGGIRPYVNV) and two for hyaluroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…venom proteins induce the production of non-neutralizing antibodies, later present in the total IgG pool of anti-venoms [32,33]. This brings upon the need for the employment of SMases D or their immunorelevant domains as major immunogens in the immunization process, given the significance of these toxins in the course of envenomation [32,[34][35][36][37]. In addition to this, over the last years, there has been a rising demand for advancements in the conception of anti-venom production.…”
Section: Discussionmentioning
confidence: 99%
“…venom proteins induce the production of non-neutralizing antibodies, later present in the total IgG pool of anti-venoms [32,33]. This brings upon the need for the employment of SMases D or their immunorelevant domains as major immunogens in the immunization process, given the significance of these toxins in the course of envenomation [32,[34][35][36][37]. In addition to this, over the last years, there has been a rising demand for advancements in the conception of anti-venom production.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a synthetic chimera containing sequences of PLDs from L. intermedia and L. laeta venoms, and sequences of a LALP and hyaluronidase isoforms from L. intermedia venom was recently constructed. This fusion molecule stimulated the production of polyclonal antibodies which recognized venoms of the different species of Loxosceles, and blocked the activities of PLDs, metalloproteases and hyaluronidases present in the venoms [107].…”
Section: A New Generation Of Anti-loxoscelic Sera and Vaccines Using mentioning
confidence: 99%
“…This would allow PLDs recognition of different species of Loxosceles spiders, and also the possibility of using monoclonal antibodies for sandwich ELISA tests. Such methods, based on the search for PLD antigens in samples collected from skin lesions of victims, could be directed to these toxins by the high biological conservation of these molecules in the different venoms [5,6] and for their high determinant antigenic properties [107].…”
Section: Diagnosis Of Loxoscelism Based On the Identification Of Pldsmentioning
confidence: 99%
“…Similarly, a major knowledge gap exists regarding the ability of available antivenoms to neutralize fibrinogenolytic effects of Loxosceles venoms. Most studies on Loxosceles antivenom, either using crude venom or recombinant toxins, focus on the necrotizing effects of the venom rather than coagulotoxic effects [25][26][27][28][29]. This is reflected in the antivenom production, with the immunizing mixture typically being recombinant spider sphingomyelinase D toxin, not crude (whole) venom due to the impracticality of collecting large quantities of spider venom.…”
Section: Introductionmentioning
confidence: 99%
“…One study showed a polyvalent serum from rabbits using a combination of SMase D toxins, hyaluronidases, and LALPs. The authors suggested that this serum was able to prevent fibrinogen alpha-chain digestion using 100 µL of serum to target 3 µL of L. intermedia venom [29]. This high serum:antivenom ratio indicates poor neutralization capacity of this antivenom.…”
Section: Introductionmentioning
confidence: 99%